Single-Nucleotide Polymorphism Leading to False Allelic Fraction by Droplet Digital PCR. (6th January 2020) - Christenson, Eric S; Dalton, W Brian; Chu, David; Waters, Ian; Cravero, Karen; Zabransky, Daniel J; DeZern, Amy E; Park, Ben H o
Abstract: BACKGROUND: Molecular-based diagnostics have great utility for cancer detection. We have used droplet digital PCR (ddPCR) as a platform for identifying mutations in circulating plasma tumor DNA (ptDNA). We present the unexpected finding of a spurious mutant allele fraction that was discovered to be artifactual because of the presence of a single-nucleotide polymorphism (SNP) in a patient sample. DESIGN AND METHODS: Probe and primer combinations for the K700 and V701 loci of the SF3B1 spliceosome gene were designed for ddPCR to identify the percentage of mutant and wild-type alleles. Clinical samples from patients with cancer with known SF3B1 mutations were collected and tested to evaluate the assays' ability to detect SF3B1 mutations in ptDNA. RESULTS: Patient samples showed SF3B1 K700E mutations within the ptDNA of 4 patients with acute leukemia and 3 with myelodysplastic syndrome who were known to harbor this mutation. A blood sample from a patient with lung cancer with a known SF3B1 V701F mutation was also analyzed and this mutation was successfully identified in ptDNA. However, 1 of the patients with a K700E mutation was found to have a mutational burden of 98%. After careful analysis of this locus by Sanger sequencing and ddPCR, this patient was found to have an SNP (R702R), which prevented binding of the ddPCR wild-type probe to its cognate allele. CONCLUSIONS: These results further support that ddPCR-based assays may be valuable companion diagnostics for the identification and monitoring of patients with cancer, but the results also emphasize the need to identify SNPs at loci that are being analyzed.